Does Metformin in Different Doses Cause Vitamin B12 Deficiency? A cross-Sectional Study: Metformin And Vitamin B12 Deficiency - Mohammed Ismail, Serwan (Cellular and Molecular Biology, 2023)
The use of metformin in diabetic patients causes vitamin B12 deficiency, but there is not enough evidence about the existence of a correlation between different doses of metformin and vit B12 deficiency. Therefore, this study was conducted with the aim of investigating the correlation between different doses of metformin and vitamin B12 deficiency. This cross-sectional study was conducted on 200 patients with type 2 diabetes referred to the diabetes clinic of the central hospital of Sulaimani city in 2022. Demographic data were collected by a questionnaire and the serum level of Vit B12 data was by testing the blood samples. Data analysis was done using SPSS ver.23 and descriptive tests, chi-square, Pearson correlation and logistic regression. The results showed that 24% of patients had vitamin B12 deficiency. 45 (93.8%) patients with vitamin B12 deficiency have taken metformin. The mean vitamin B12, mean metformin consumption per year and metformin dose were significantly different between the two groups. Based on the regression model, it was shown that there was no significant relationship between the serum level of vitamin B12 and the duration of metformin medication (P=0.134). And the relationship between gender, occupation, alcohol and metformin dose (mg) was significant, so these factors have the ability to predict the serum level of vitamin B12. The results showed that vitamin B12 deficiency is common in diabetic patients who take metformin, and the vitamin deficiency will increase with the increase in the dosage.